Bioacumulação de mercúrio no gradiente estuarino do rio Jaguaribe, CE - Moura, Victor Lacerda (2017)
Extensive changes in the natural landscape in the Lower Basin of the Jaguaribe River, as the construction of dams, together with scarcer annual rainfall due to Global Changes, contribute to a greater residence time of the water masse in the estuarine region, enabling greater mobility and reactivity of the mercury emitted by anthropic activities in the environment. However, despite the small mercury loads launched by these activities, natural estuarine characteristics, global climatic changes and regional anthropic modifications contribute to an increase in the production and bioavailability of mercury to the trophic web in this ecosystem. Therefore, aiming to understand the influence of biological and environmental factors in the variation of mercury concentrations in the aquatic faunal along the estuarine gradient of the Jaguaribe river, two campaigns were conducted in 2015 at five points distributed along the estuarine region. Two of these points were located in the area of dominant river influence and three in the area of dominant marine influence, where fish, crustaceans and mollusks species were collected for identification, biometric data record and analysis of the total mercury concentration present in the muscle tissue of these organisms. 830 organisms of 16 species were collected, nine species of vertebrates, consisting of finfish (Osteichthyes, Actinopterygii) and seven species of invertebrate, four of crustaceans (Decapoda) and three of mollusks (one Gastropoda and two Bivalves). The highest concentrations were observed, for invertebrates, the crabs Callinectes bocourti (Decapoda, Portunidae) (201 ng.g-1) and Callinectes larvatus (Decapoda, Portunidae) (104 ± 43 ng.g-1), and for fishes Elops saurus (Elopiformes, Elopideae) (109 ± 15 ng.g-1) and Menticirrhus americanus (Perciformes, Sciaenidae) (104 ± 30 ng.g-1), on species of carnivorous habit. The bioaccumulation curves for the carnivorous species presented positive values, although with a weak correlation, thereby proving a process of bioaccumulation of mercury with the increase of size. However, some species of different food habits showed decreasing curves in the morphometric ratio and concentration of total mercury. The intraspecific comparative analysis between zones under fluvial and marine influence showed that the species collected in the area of dominant marine influence had higher concentrations of mercury than the same species in the area of dominant river influence. It is soon possible to conclude that the biological factors such as food habit, trophic position and biometric data were determinant in the variations of concentration of total mercury between individuals of the same species and distinct species. However, in addition to the biological factors, the environmental aspects also presented important results, evidencing their relevance in determining the concentrations of total mercury along the estuarine gradient.